Comparative Study of the Pregnancy Outcomes in Nulliparous Women over and Under Age 35 - Azar Aghamohammadi; Maryam Nooritajer; Masoume Kheyrkhah; Agha Fateme Hoseyni (نشریه پرستاری ایران, 2010)
Background and Aim: Nowadays, lots of women defer child bearing even until the age 40 due to the job, economy and education reasons. Therefore, protecting mothers and new-born babies health requires experts and midwifes to increase their knowledge about the outcome of such pregnancies. This study aims at comparing the outcome of the pregnancy in nulliparous women who were over and under age 35.   Material and Method: This study was a descriptive-comparative study and included 509 sample cases of first-time delivery that were given birth from March 2000 to March 2007 with gestational age over 24 weeks whose records were available in Hospital. The samples were divided into two groups of over 35 and 20 - 34 years old and the consequences of the pregnancy were compared. Chi-square and Fisher tests and Odds-ratio were used to analyze the data.   Results: There was a statistically significant relationship between age over 35 and preeclampsia, premature delivery, malpresentation, caesarian and low birth weight.   Conclusion: Pregnancy over the age 35 can be considered a dangerous kind and regarding the increase in the marriage age, it is required that people in charge of hygienic centers pay more attention to increasing the knowledge among the women and midwifes in order to have a more healthy generation.